A switch from parallel to antiparallel strand orientation in a coiled‐coil X‐ray structure via two core hydrophobic mutations. Issue 3 (May 2015) - Malashkevich, Vladimir N.; Higgins, Chelsea D.; Almo, Steven C.; Lai, Jonathan R.
ABSTRACT: The coiled‐coil is one of the most ubiquitous and well studied protein structural motifs. Significant effort has been devoted to dissecting subtle variations of the typical heptad repeat sequence pattern that can designate larger topological features such as relative α‐helical orientation and oligomer size. Here we report the X‐ray structure of a model coiled‐coil peptide, HA2‐Del‐L2seM, which forms an unanticipated core antiparallel dimer with potential sites for discrete higher‐order multimerization (trimer or tetramer). In the X‐ray structure, a third, partially‐ordered α‐helix is weakly associated with the antiparallel dimer and analytical ultracentrifugation experiments indicate the peptide forms a well‐defined tetramer in solution. The HA2‐Del‐L2seM sequence is closely related to a parent model peptide, HA2‐Del, which we previously reported adopts a parallel trimer; HA2‐Del‐L2seM differs by only hydrophobic leucine to selenomethione mutations and thus this subtle difference is sufficient to switch both relative α‐helical topology and number of α‐helices participating in the coiled‐coil. Comparison of the X‐ray structures of HA2‐Del‐L2seM (reported here) with the HA2‐Del parent (reported previously) reveals novel interactions involving the selenomethionine residues that promote antiparallel coiled‐coil configuration and preclude parallel trimer formation. These novel atomic insights are instructive for understanding subtle features that can affect coiled‐coil topology and provide additional information for design of antiparallel coiled‐coils. © 2015 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 104: 178–185, 2015.